Certain aspects of working capital in a construction company - Meszek, Wiesław; Polewski, Marcin (Technological and Economic Development of Economy, 2006)
The article analyses the profiles of selected construction companies from the viewpoint of working capital formation and their management strategies applied to working capital. The analysis was performed on the basis of financial ratios. The conclusion is that complex working capital management requires controlling methodology to be developed. A specific character of the construction industry, including operational factors and market requirements, make working capital management a task exceeding the financial sphere, as it embraces the issues of organisation of investment processes, the organisation of production processes and logistics.Apyvartinio kapitalo rodikliai statybos įmonėjeSantrauka. Šiame straipsnyje, nagrinėjant finansinius rodiklius, analizuojamas pasirinktų statybos įmonių apyvartinio kapitalo formavimas ir jo valdymo strategijos. Atlikta finansinių rodiklių analizė. Daroma išvada, jog kompleksiniam apyvartiniam kapitalui valdyti turi būti sukurta kontrolės metodologija. Dėl gamybos, rinkos ir kitų veiksnių statybos pramonės įmonėse apyvartinio kapitalo valdymas peržengia finansinę sferą, nes apima investavimo, gamybos ir aprūpinimo procesų organizavimą.Reikšminiai žodžiai: apyvartinis kapitalas, grynųjų pinigų apyvartumas, likvidumo rodiklis, dabartiniai aktyvai, galimybe įvykdyti trumpalaikius įsipareigojimus.First Published Online: 21 Oct 2010